VIS-NIR spectral and particles distribution of Au, Ag, Cu, Al and Ni nanoparticles synthesized in distilled water using laser ablation - Mas Ira Syafila, Mohd Hilmi Tan; Ahmad Fairuz, Omar; Marzaini, Rashid; Uda, Hashim (Elsevier B.V., 2019)
In this research, gold (Au), silver (Ag), copper (Cu), aluminium (Al) and nickel (Ni) nanoparticles have been prepared by laser ablation in distilled water using Q-switched Nd: YAG. Comparative analysis between 1064 nm and 532 nm laser wavelength in term of absorption spectra and particle size distribution is performed. The synthesized nanoparticles were characterized by visible (VIS) and near infrared (NIR) spectrometer and transmission electron microscopy (TEM). The effect of laser pulse energy and laser wavelength on the size distribution and absorbance spectrum of metal nanoparticles was studied. The absorption peak intensities of the nanoparticles increase at higher laser pulse energy. It is discovered that for all metals, 532 nm laser produced nanoparticles with higher absorption peak intensities than 1064 nm. The work also shows that there is no noticeable difference in the size of the nanoparticles produced at 532 and 1064 nm for the Ni and Cu metals. However, a considerable size difference can be seen for Au, Ag, and Al at the two laser wavelengths. Smaller Ag nanoparticles were produced by 1064 nm laser while smaller Au and Al nanoparticles were produced by 532 nm laser.